2023
DOI: 10.3389/fonc.2023.1111522
|View full text |Cite
|
Sign up to set email alerts
|

Emerging functions of C/EBPβ in breast cancer

Abstract: Breast tumorigenesis relies on complex interactions between tumor cells and their surrounding microenvironment, orchestrated by tightly regulated transcriptional networks. C/EBPβ is a key transcription factor that regulates the proliferation and differentiation of multiple cell types and modulates a variety of biological processes such as tissue homeostasis and the immune response. In addition, C/EBPβ has well-established roles in mammary gland development, is overexpressed in breast cancer, and has tumor-prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 117 publications
0
3
0
Order By: Relevance
“…Using a cytokine/chemokine array, we detected an elevated level of IFNβ in 2208L tumors treated with IACS-70654 as compared to controls treated with vehicle ( Figure 5E ). IACS-70654 also downregulated genes involved in the regulation of inflammation and inhibition of cytokine production, such as Cd200 and Cebpb which have been shown to induce immunosuppression in the TIME (Choe and Choi, 2023, Matherne et al, 2023) ( Figure 5A and Supplemental S5C). In tumor cells, these results showed that in 2208L tumor cells IACS-70654 induced both MHCI expression and an IFN response, suggesting induced antigen presentation and immune stimulation including T-cell activation.…”
Section: Resultsmentioning
confidence: 99%
“…Using a cytokine/chemokine array, we detected an elevated level of IFNβ in 2208L tumors treated with IACS-70654 as compared to controls treated with vehicle ( Figure 5E ). IACS-70654 also downregulated genes involved in the regulation of inflammation and inhibition of cytokine production, such as Cd200 and Cebpb which have been shown to induce immunosuppression in the TIME (Choe and Choi, 2023, Matherne et al, 2023) ( Figure 5A and Supplemental S5C). In tumor cells, these results showed that in 2208L tumor cells IACS-70654 induced both MHCI expression and an IFN response, suggesting induced antigen presentation and immune stimulation including T-cell activation.…”
Section: Resultsmentioning
confidence: 99%
“…Gene ontology analysis of these genes showed that 23 of them encode DNA-binding proteins, particularly enriched with zinc-finger TFs (see Additional file 1 : Table S6). A number of these, such as CEBPB, ZNF117 and ZNF92, have been previously proposed as breast cancer markers [ 41 43 ] and ZNF273 and ZNF727 have been reported as breast cancer hub genes [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, these pathways are well-described as oncogenic in specific contexts, predominantly c-JUN [25], IL-6/JAK/STAT3 [26], and TGFβ [27]. C/EBPβ seems to exert an isoform-specific oncogenic role in breast cancer [28]. However, in certain malignancies, these molecules can exert anti-tumor properties in a context-dependent and tumor-stage-dependent manner as well.…”
Section: Discussionmentioning
confidence: 99%
“…C/EBPβ seems to exert an isoform-specific oncogenic role in breast cancer (32). However, in certain malignancies, these molecules can exert anti-tumor properties in a context-dependent and tumor stage-dependent manner as well.…”
Section: Initiation Of Hnscc Differentiation Activates Wound-healing-...mentioning
confidence: 99%